Increased prevalence and geographic spread of the cardiopulmonary nematode Angiostrongylus vasorum in fox populations in Great Britain. Issue 9 (1st June 2015) - TAYLOR, C. S.; GARCIA GATO, R.; LEARMOUNT, J.; AZIZ, N. A.; MONTGOMERY, C.; ROSE, H.; COULTHWAITE, C. L.; MCGARRY, J. W.; FORMAN, D. W.; ALLEN, S.; WALL, R.; MORGAN, E. R.
SUMMARY The nematode Angiostrongylus vasorum is becoming more widely recorded globally, and is of increasing concern as a cause of disease in dogs. Apparent geographic spread is difficult to confirm due to a lack of standardized disease recording systems, increasing awareness among veterinary clinicians, and recent improvements in diagnostic technologies. This study examines the hypothesis that A. vasorum has spread in recent years by repeating the methods of a previous survey of the fox population. The hearts and lungs of 442 foxes from across Great Britain were collected and examined by dissection and flushing of the pulmonary circulation and microscopic inspection of tracheal scrapes. Sampling and parasite extraction methods were identical to an earlier survey in 2005 to ensure comparability. Prevalence of A. vasorum was 18·3% (exact binomial confidence bounds 14·9–22·3), compared with 7·3% previously (5·3–9·9, n = 546), and had increased significantly in most regions, e.g. 7·4% in the Northern UK (previously zero) and 50·8% in the south-east (previously 23·2%). Other nematodes identified were Crenosoma vulpis (prevalence 10·8%, CI 8·1–14·2) and Eucoleus aerophilus (31·6%, CI 27·3–36·2). These data support the proposal that A. vasorum has increased in prevalence and has spread geographically in Great Britain.